Strain‐induced post‐curing of acrylate networks. Issue 12 (11th February 2021) - Maassen, Eveline E. L.; Anastasio, Rosaria; Poto, Serena; Cardinaels, Ruth; Sijbesma, Rint P.; van Breemen, Lambèrt C. A.; Heuts, Johan P. A.
Abstract: The mechanical properties and network structure of photocurable polymers are strongly dependent on processing conditions. Here it is reported that highly crosslinked acrylate systems undergo unexpected additional post‐curing during DMTA measurements, resulting in an increase in glass‐transition temperature ( T g ). A detailed study of the conditions under which this increase in T g takes place unequivocally shows that a small (0.1%) oscillatory strain applied above T g is responsible for additional cross‐linking reactions. The effect of strain‐induced post‐curing is confirmed by applying post‐curing treatments under oscillatory shear strain in rheological tests. Different acrylate systems were characterized and the results show that the strain induced post‐curing depends on the network structure of the polymer. In polymer networks with an initial high crosslink density the effect is pronounced while in polymers with an initial lower crosslink density no shift in T g is observed. Abstract : The mechanical properties and network structure of photocurable polymers are strongly dependent on processing conditions. Here it is reported that highly crosslinked acrylate systems undergo unexpected additional post‐curing during DMTA measurements. This work demonstrates that the measured mechanical properties can be affected by the experimental techniques used to measure those properties.